Rapid validity testing at the front end of innovation - Birgit Pe\~na Häufler; Dietfried Globocnik; Paola Landaeta Saldías; Søren Salomo (Journal of Product Innovation Management, 2021)
To efficiently and effectively reduce the uncertainty inherent in the front-end of innovation processes, recent literature emphasizes new approaches that facilitate rapid knowledge generation and learning such as design thinking, lean innovation, and pretotyping. However, these approaches differ in their conceptualizations and, despite their popularity, the empirical evidence on the performance relevance of such approaches for established organizations is limited. In this research, we propose rapid validity testing (RVT), in which we conceptualize and harmonize existing approaches toward a unique and comprehensive set of front-end activities necessary to reduce uncertainty and equivocality inherent to this phase and enable planned flexibility. Drawing on information processing theory, we argue that organizations implementing RVT also increase the probability of achieving innovation outcomes of superior quality on time and within budget. We further argue that the effectiveness of RVT depends upon internal and external environmental factors. Drawing on multirespondent data collected from 1022 informants in 129 firms, we find empirical evidence that organizations implementing the RVT approach in their innovation activities achieve higher performance of their innovation programs, and that the performance relevance of RVT depends upon technological turbulence and the organization's long-term orientation and risk propensity. We contribute to the literature by conceptualizing RVT as a set of activities that enable planned flexibility. Furthermore, we overcome empirical shortcomings of studies on popular approaches that relied primarily on anecdotal or case study evidence and imply the generalizability of their effectiveness. Our findings highlight that organizations indeed not only benefit from RVT but also challenge the notion of a one-size-fits-all approach to the front end of innovation.
Keywords: 650; environmental turbulences; experimentation; formalization; front end; innovation process; organizational culture; planned flexibility; prototyping; rapid validity testing